Human-environmental interactions in Mediterranean climate regions from the Pleistocene to the Anthropocene. (September 2020) - Rick, Torben; Ontiveros, Miguel Ángel Cau; Jerardino, Antonieta; Mariotti, Annarita; Méndez, César; Williams, Alan N.
Highlights: Climate change poses great challenges for human welfare and biodiversity in Mediterranean Climate Regions. Archaeological and paleoecological records document human responses to past climate change. Past climatic deterioration was an important driver of socio-environmental change. People actively altered ecosystems and landscapes in these regions for millennia. Archaeological records provide key insights for preparing for climate and environmental challenges of the future. Abstract: From mobile hunter-gatherers to a series of state societies, Mediterranean climate regions (MED) around the world have been critical areas for human and biological evolution for millennia. Comprised of five regions on six continents, the MED are important today for human settlement, global food production, transportation, industry, and tourism, but these regions are also extremely vulnerable to projected changes in their typically temperate climate towards more extreme conditions. Researchers and strategists are exploring the implications of these changes for present and future societies, but there has been limited comparative synthesis of past human responses to environmental and climatic change in the global MED and how these data may help prepare and plan for projected changes in the future. This review synthesizes archaeological and paleoenvironmental data, focusing on key demographic, social, economic, and cultural developments that occurred alongside and often in response to past climate and environmental disruption. Past climatic change influenced broader socio-environmental systems, in some cases acting as a driver of population collapse, large-scale abandonment, migration, and socio-political upheaval. These deep time data illustrate the importance of understanding Pleistocene-Holocene human-environmental interactions, land use, and climate change to help evaluate and plan for contemporary and projected environmental change.